KESELARASAN ANTARA DOUTOKU KYOUIKU DAN KYUUSHOKU PADA PENDIDIKAN DASAR DI JEPANG - SRI PANGASTOETI (Japanology: The Journal of Japanese Studies, 2025)
Moral education (doutoku kyouiku) is fundamental in shaping students’ characters so that they become independent individuals who are able to adapt to their social environment in accordance with the values that prevail in society. This article aims to examine the implementation of moral education at the elementary education level in Japan, as well as its integration into kyuushoku (school lunch) activities. This study uses a literature review method based on curriculum documents, education regulations, and previous research results. The results show that moral education (doutoku kyouiku) and school lunch practices (kyuushoku) in primary and secondary education in Japan are designed in an integrated manner, with doutoku providing a framework of values and kyuushoku embodying them in shared meals that cultivate responsibility, discipline, gratitude, ecological awareness, and cross-cultural openness. Kyuushoku has evolved from a nutritional fulfillment program into a hidden curriculum that integrates moral values, health, national identity, and sustainability through shokuiku policies and inter-ministerial collaboration. The integration of the two at the compulsory education level makes doutoku–kyuushoku a driving force in shaping the character of Japanese citizens who are healthy, locally rooted yet cosmopolitan, and contribute to the development of Japan’s social capital.